A memorable experience in the metaverse led to a desire to revisit: the moderate role of Kama Muta, arousal and dominance. - Ferreira, Mónica Mendes; Loureiro, S. M. C.; Bilro, R.G. (8th International XR-Metaverse XR meets the Metaverse, 2023)
This research intends to explore the customer experience and human-computer interaction further (e.g., Flavian et al., 2019, Jung et al., 2020; Loureiro et al., 2019; Tom Dieck & Han, 2022) using a VRChat scenario with a landscape and restaurants representing a virtual and new tourism destination. Researchers have developed two distinct studies to achieve this purpose. The first study explores the interaction inside a VRChat scenario to understand the avatar interaction during the visit inside the VRChat scenario. A group of 6 to 8 participants, and their avatars, are conducted to interact in the VRChat scenario, followed by a focus group to explore the dimensions of a memorable experience in the interaction process. Data is treated using MXQDA and text mining. The subsequent study intends to explore the effect of a memorable tourism experience (Kim et al., 2012) on the intensification and desire to revisit (De Rojas & Camarero, 2008), through Kama Muta’s emotional state, arousal, and dominance (Roschk et al., 2017). The data collection uses prolific to a panel sample of users who interacted in the VRChat scenario. This research results give insights into how experience enhances emotional states in new and virtual environments, contributing to managers and society.